Rosmarinic Acid Exhibits Antifungal and Antibiofilm Activities Against Candida albicans: Insights into Gene Expression and Morphological Changes - Merve Aydin; Nurhan Unusan; Esra Sumlu; Emine Nedime Korucu (Journal of Fungi)
Candida species, opportunistic pathogens that cause various infections, pose a significant threat due to their ability to form biofilms that resist antifungal treatments and immune responses. The increasing resistance of Candida spp. and the limited availability of effective treatments have prompted the research of natural compounds as alternative therapies. This study assessed the antifungal properties of RA against Candida species, focusing on its impact on C. albicans biofilms and the underlying mechanisms. The antifungal efficacy of RA was evaluated using the CLSI M27-A3 microdilution method on both fluconazole-susceptible and -resistant strains. Biofilm formation by C. albicans was assessed through a crystal violet assay, while its antibiofilm activity was analyzed using an MTT assay and field emission scanning electron microscopy (FESEM). Gene expression related to biofilm formation was studied using quantitative real-time PCR (qRT-PCR), and statistical analysis was performed with an ANOVA. Among the 28 Candida strains tested, RA exhibited minimum inhibitory concentration (MIC) values ranging from 160 to 1280 μg/mL. At a 640 μg/mL concentration, it significantly reduced the expression of genes associated with adhesion (ALS3, HWP1, and ECE1), hyphal development (UME6 and HGC1), and hyphal cAMP-dependent protein kinase regulators (CYR1, RAS1, and EFG1) in RAS1-cAMP-EFG1 pathway (p < 0.05). FESEM analysis revealed a reduction in hyphal networks and disruptions on the cell surface. Our study is the first to demonstrate the effects of RA on C. albicans adhesion, hyphae development, and biofilm formation through gene expression analysis with findings supported by FESEM. This approach distinguishes our study from previous studies on the effect of RA on Candida. However, the high MIC values of RA limit its antifungal potential. Therefore, more extensive research using innovative methods is required to increase the antifungal effect of RA.